The Socialist market economy in Asia : development in China, Vietnam and Laos - Hansen, Arve.; Bekkevold, Jo Inge.; Nordhaug, Kristen (Singapore : Palgrave Macmillan, 2020)
'Here is an excellent comparative analysis of development in Asia's reform-era communist societies. The authors add much to our understanding of the experiences and prospects of China, Vietnam, and Laos. Of equal importance, the comparison of the three helps to differentiate the successes and challenges of their political economic models from the idiosyncrasies of situation and leadership.' Brantly Womack, C. K. Yen Professor of Foreign Affairs, University of Virginia, USA 'China, Laos and Vietnam are evidently markedly different but they share a common commitment to socialist market development. This book ambitiously brings their experiences of transformation into conversation, connecting the planning, governance and politics of such development with its outcomes in terms of society and environment. It holds important lessons for theory and practice, and for countries beyond these three socialist states.' Jonathan Rigg, Professor and Chair in Human Geography, University of Bristol, UK This book is intended for policy-makers, academics and students of development studies, area studies, political economy, geography and political science. Three of the best global performers in terms of economic growth are authoritarian states led by communist parties. The 'socialist market economy' model employed in China, Vietnam and Laos performs better than the economic systems in countries at a similar level of income per capita on a wide range of development indicators, yet market reforms and governance failures have led to highly unequal societies and significant environmental problems. This book presents the first comparative study of development in these three countries. Written by country experts and scholars of development studies, it explores the ongoing quest for market versus state within their model, and the coherence of their development. Arve Hansen is a Postdoctoral Fellow at the Centre for Development and the Environment at the University of Oslo. He has a decade of experience working on development in Vietnam. Jo Inge Bekkevold is a Senior Adviser at the Norwegian Institute for Defence Studies. He was previously a career diplomat, with postings to China and Vietnam. Kristen Nordhaug is a Professor of Development Studies at Oslo Metropolitan University. His work focuses on political and economic development in East and Southeast Asia.
Part I: The socialist market economy: ideology and development -- Chapter 1: Introducing the socialist market economy -- Chapter 2: The international politics of economic reforms in China, Vietnam and Laos -- Part II State, market and the environment -- Chapter 4: Governance, the socialist market economy, and the party-state in Vietnam and China -- Chapter 5: Reforming state-owned enterprises in a global economy: the case of Vietnam -- Chapter 6: Rural revolutions: socialist, market and sustainable development of the countryside in Vietnam and Laos -- Chapter 7: Evolving environmental governance structures in a market socialist state: the case of Vietnam -- Part III State and society: inequality, class and conflict -- Chapter 8: Consumer socialism: consumption, development and the new middle classes in China and Vietnam -- Chapter 9: Labour conflicts in the socialist market economy -- China and Vietnam -- Chapter 10: Welfare and social policy in China - building a new welfare state -- Chapter 11: Capitalist transformation and habitus in Laos -- Part IV Concluding observations -- Chapter 12: Making sense of the socialist market economy.
Includes bibliographical references and index.
Keywords: Economic development -- Political aspects -- China; Economic development -- Political aspects -- Vietnam; Economic development -- Political aspects -- Laos; Communism -- China; Communism -- Vietnam; Communism -- Laos; China -- Economic conditions; Vietnam -- Economic conditions; Laos -- Economic conditions